THE EFFECTIVENESS OF ACUYOGA POSTPARTUM ON PRIMIPAROUS POSTPARTUM PAIN WITH PERINEAL TRAUMA - Lydia Febrina Sipahutar; Lucky Herawati; Melyana Nurul Widyawati (Alta Dharma Publisher, 2019)
Perineal trauma commonly impacts on childbirth women due to laceration or intentional because of an episiotomy. The study aimed to examine the effect of AcuYoga postpartum on decreasing the pain among primiparous postpartum with perineal trauma. A quasi-experimental, pre-test, and post-test design with a non-equivalent control group were applied in this study. Thirty-four samples were allocated to the experimental and control groups. The experimental group received the AcuYoga postpartum, and the control group received the general postnatal exercises. The findings showed that there are significant differences in pain levels among the experimental group who received the program than a control group who receive routine care (p-value<0.05). There are significant differences in pain levels among the experimental group before and after program implementation (p<0.05). Further studies need to examine Acuyoga on other variables such as duration of perineal wound healing, the process of elimination, and clinical biomarkers Keywords: Acuyoga, exercise, primipara, pain, perineal trauma